THE EFFECTIVENESS OF PSYCHOLOGICAL COUNSELING SESSIONS IN DEVELOPING SELF-CONFIDENCE AMONG FEMALE FITNESS TRAINEES IN GYMS - Marwah Ali Hamzah (Universitas Negeri Jakarta, 2026)
Background. The psychological preparation of athletes has become an urgent necessity, given the training pressures they face and the diverse sources of these pressures. Objectives. The purpose of this paper is to develop psychological counseling sessions to enhance self-confidence among female fitness trainees in gyms. It also sought to identify existing psychological counseling sessions designed to foster self-confidence in these women. Method. A two-group experimental design with pre- and post-testing was employed, deemed suitable for the nature of the research problem. The research community consisted of 23 female fitness trainees at Samana Beauty Gym in 2024. A census was used to select a 100% sample from this community, which was then randomly divided into two groups: an experimental group and a control group, each containing 10 trainees. The Robin Velley Self-Confidence Scale, translated into Arabic by Mohammed Hassan Alawi and comprising 13 items, was selected for this purpose. After completing these procedures, the researcher conducted the psychological counseling sessions with the trainees for one month, with three sessions per week (Sunday, Tuesday, and Thursday) before each training session, each lasting 30 minutes. The total number of sessions was 12. Results. The results of the study showed a significance value (p<0.05) which means that there was a significant influence of using both psychological counseling sessions (experimental group) and the control group in developing self-confidence among female fitness training participants. Conclusion. Resistance exercise programs using single and double weight machines enhanced maximal The most important conclusions reached were that the psychological counseling sessions had a clear impact on developing self-confidence among the fitness trainees in gyms, and that these sessions played a significant role in motivating the trainees to perform their physical exercises fully and without hesitation.